(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A ruling that reestablishes the marital bond between a couple who has been legally separated is known as the “restitution of conjugal rights”. The primary purpose of the decree is to protect the conjugal rights of the couple; nonetheless, this provision compels an individual to cohabit with other people, regardless of whether or not they like to do so. Does this decision go against the principles of the “right to privacy” that each spouse is guaranteed by the constitution? Regarding this matter, the SC stated that the main purpose is the couple’s ability to continue living together. In spite of this fact, the SC of India failed to recognise that it was interfering with the personal liberty of a person and taking away his or her “right to privacy”. This occurred despite the fact that morality and good conscience, sexual autonomy, and the dignity of a person are all extremely important factors to consider.